Dietary trigger factors of migraine and tension-type headache in a South East Asian country - Tai, Mei Ling Sharon; Yap, Jun Fai; Goh, Cheng Beh (Dove Medical Press, 2018)
Background: The literature on the dietary trigger factors of headache among the South East Asians is limited. Objective: The objective of the study was to examine the dietary trigger factors of migraine and tension-type headache (TTH) in Malaysian patients, consisting of Malays, Chinese and Indians. Methods: In this prospective cross-sectional study, patients presenting with migraine and TTH to a neurology clinic between April 2010 and June 2017 were recruited. The patients were given a comprehensive dietary list consisting of 25 specified types of food and drink items as well as other unspecified types of food and drink items which were possible dietary triggers. The data on these dietary triggers and missing meals were collected. Results: A total of 684 patients with headache (319 migraine and 365 TTH patients) were recruited. One hundred and fifty-eight (23.1%) patients had missing meals as trigger. Two hundred and fifty-five (37.3%) patients had dietary triggers; 141 (44.2%) patients with migraine and 114 (31.2%) patients with TTH had dietary triggers. Eighty-four (52.8%) Malay, 28 (41.8%) Chinese, 25 (32.5%) Indian migraine patients and five (38.5%) migraine patients from other ethnic groups, had dietary triggers. Some 58 (40.0%) Malay, 27 (25.2%) Chinese, 22 (23.9%) Indian patients and 7 (29.2%) patients from other ethnic groups with TTH had dietary triggers. The most common dietary trigger factors were coffee (19.9%), chocolate (7.5%) and food rich in monosodium glutamate (5.6%). Logistic regression showed that chocolate (OR 2.16, 95% CI 1.06–4.41, p = 0.035) and coffee (OR 1.73, 95% CI 1.12–2.68, p = 0.014) were significantly associated with migraine compared to TTH. Conclusion: Chocolate and coffee significantly triggered migraine compared to TTH. Inter-ethnic differences were observed for dietary trigger factors.